Relationship between malondialdehyde activity (MDA) &Lipid Profile in Diabetic Patients - Salih Hamad, Mahde; Jasim Khalaf, Salim; Riffat Sarhat, Entedhar (Tikrit Journal of Pharmaceutical Sciences, 2023)
The current investigation was designed to seek for the relationship of malondialdehyde (MDA) with the parameters of serum lipid profile in diabetes mellitus. To achieve this purpose, 55 diabetics (l I IDDM patients and 44 NIDDM patients) and 25 age matched healthy subjects were enrolled. lt was found that significant (P<0.001) elevations of MDA, S.Tc, S.Tg, LDl-cholesterol and VLDLtriglycerides in both types of diabetics when compared with those of the healthy individuals.The correlation analysis established marked conelation of MDA with S.Tc, STg, and LDl-cholesterol levels in two types of diabetics while VLDLtriglycerides demonstrated obvious correlation with MDA in IDDM. The result pointed out the interrelation ships of MDA with serum lipid profile in diabetes mellitus.